Equal channel angular extrusion for bulk processing of Fe–Co–2V soft magnetic alloys, part I: Processing and mechanical properties. Issue 15 (21st May 2018) - Susan, Don F.; Jozaghi, Taymaz; Karaman, Ibrahim; Rodelas, Jeff M.
Abstract: Abstract : The soft magnetic alloy Fe–Co–2V, also known as Permendur-2V or Hiperco® 50A, was subjected to equal channel angular extrusion (ECAE) at 750–850 °C using two processing routes. Hiperco is a trade name of Carpenter Technology Corporation. ECAE, which is a severe plastic deformation process, refined the grain size to about 1.5–3 μm, compared to 25–70 μm for the conventional Hiperco® bar. The fine-grain microstructure is homogenous throughout the ECAE material, from center to edge, due to the simple-shear ECAE process. Fine-grained Hiperco® has previously only been obtainable in the sheet form. ECAE resulted in yield and tensile strengths of 650–700 MPa and 900–1400 MPa, respectively, representing a 2–3-fold strength increase compared to the conventional bar. The yield strength was demonstrated to fit well to the Hall–Petch relationship established using previous reports on the strength of conventional bar and sheet materials. High ductility, up to 18%, was obtained in the ECAE processed billets and attributed primarily to the partially disordered bcc crystal structure upon quenching from ECAE.